Evaluation of the quality of commercial starter derivatives for use in yoghurt beverage products - Amaniyah Maghfirotul; Devitasari Ajeng; Br Bangun Jesika Putri; Priyadi Dwi Ahmad; Prayitno Salvian Setyo (BIO Web of Conferences)
The starter used in yogurt beverage production influences its physicochemical properties, microbiological composition, and sensory quality. While using starter derivatives can reduce production costs, a challenge arises in that they may alter their adaptability to different production conditions and affect the characteristics of the fermented product, such as its acidity and taste. The acidic environment prolongs yogurt’s shelf life by inhibiting the growth of pathogenic bacteria, enhancing dairy products’ safety, and promoting better health. This study examined the physicochemical and microbiological properties and the sensory qualities of yogurt produced using starters derived from F1 to F4. The results indicated that the survival of lactic acid bacteria (LAB) in the yogurt starter and its derivatives remained stable. A pH decrease and total acid increase were observed from F1 to F4. Additionally, the viscosity of the derivative starters decreased, and the sensory evaluation revealed that flavor, smell, and texture significantly influenced overall acceptability. The quality yogurt made from starter derivatives no less than commercial starter and was found to be acceptable for use in yogurt beverage products.